APLIKASI GAME SEJARAH INDONESIA KELAS 2 SD BERBASIS ANDROID DI KECAMATAN PADEMANGAN - Ricardo, Deddy; Christianto, Kevin (Jurnal Teknoinfo, 2024)
Based on the provided text, it seems to be a discussion about the importance of history education and the development of a history learning application for elementary school students in Indonesia. The text highlights the concern that many students are more interested in popular TV shows and social media content rather than learning about their country's history. The lack of interest in history is attributed to the limited and formal teaching methods used in classrooms, which leads to boredom among the younger generation. The development of the history learning application is done using the Game Development Life Cycle (GDLC) with four important stages: Analysis, Production, Testing, and Release. The application is built using Unity and is targeted for 2nd-grade elementary school students at Santo Lukas I in the Pademangan District. The requirements for the application were obtained through a questionnaire with 33 participants. The research concludes that the "Sejarah Indonesia" game application based on Android using Unity and C# was successfully implemented, meeting all the specified requirements from the 33 questionnaire respondents. The writer suggests that future researchers should work on improving and addressing any shortcomings in this study